The Influence of Short Video Music on the Development of Middle School Students’ Mental Health: Exploring the New Music Classroom from the Perspective of Music Psychology - Zhang, Zhe (Transactions on Social Science, Education and Humanities Research, 2024)
Short video music has a greater and deeper impact on the daily life of junior high school students. In order to explore the causes of its formation, from the perspective of music psychology and therapy, from the characteristics of short video music and junior high school students’ psychological development, this paper analyzes how short video music affects the ears of teenagers. Under the influence of mass media, whether music teachers can make use of these characteristics to better apply them to the classroom. How to use short video music as a "double-edged sword" has become one of the important research topics in music teaching.